2014
DOI: 10.1007/s10529-014-1500-y
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture

Abstract: In this study, 3D culture system for human adipose-derived stem cell (hASC) using a BioLevitator as the bioreactor for microcarrier-based cultures was established. During the culturing period, hASCs preferred to grow in crevices between microcarriers and a high viability was maintained even when reaching confluency. Adipogenic or osteogenic differential medium was used to induce hASCs and differential potentials of these cells were compared between 2D and 3D environments via RT-PCR and staining quantifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
2
10
0
2
Order By: Relevance
“…Quantification of Alizarin Red S in stained samples demonstrated significant increases in calcium deposition by EADSC differentiated in 3D culture at weeks 2 and 3, with a further increase in calcium deposition from week 2 to week 3. Similar results have been observed during 3D culture of human adipose-derived stem cells using a bioreactor/microcarrier-based culture system, with Alizarin Red S staining demonstrating significant increases in osteogenic differentiation between 2D and 3D culture at weeks 2 and 3 (Lin et al 2014).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Quantification of Alizarin Red S in stained samples demonstrated significant increases in calcium deposition by EADSC differentiated in 3D culture at weeks 2 and 3, with a further increase in calcium deposition from week 2 to week 3. Similar results have been observed during 3D culture of human adipose-derived stem cells using a bioreactor/microcarrier-based culture system, with Alizarin Red S staining demonstrating significant increases in osteogenic differentiation between 2D and 3D culture at weeks 2 and 3 (Lin et al 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Three-dimensional culture has long been appreciated for its ability to study the growth, proliferation, and differentiation of cells in conditions that simulate the in vivo environment (Edelman and Keefer 2005). While there is a vast array of reports detailing the behaviour of bone marrow-derived mesenchymal stem cells in 3D culture, studies demonstrating the effects of 3D culture on adipose-derived stem cells are limited (Cheng et al 2012;Flynn et al 2007;Gabbay et al 2006;He et al 2010;Kisiday et al 2008;Lin et al 2014;Mauney et al 2007;Neofytou et al 2011;Rubin et al 2007). Specifically, there is only one published example of 3D culture of EADSC, detailing their encapsulation in agarose and self-assembling peptide hydrogels and subsequent chondrogenic differentiation (Kisiday et al 2008), however the authors made no direct comparison between 2D and 3D culture conditions, as was achieved in this study.…”
Section: Discussionmentioning
confidence: 99%
“…More and more researches adopt 3D scaffolds for stem cell culture. Some studies have shown that the proliferation and differentiation potential of ASCs is significantly stronger than that in 2D environment when cultured about 21 days [129,130]. 3D environment prevented the reduction of osteogenic differentiation efficiency of stem cells caused by aging or passage [130].…”
Section: Stiffness Effectsmentioning
confidence: 99%
“…scaffolds by promoting the exchange of nutrients and waste, as well as by providing mechanical stimulation that can modulate cell function [38][39][40] . Stirred culture systems, such as spinner flasks, have been most extensively explored for the expansion of mesenchymal stromal cell (MSC) populations including ASCs, incorporating a range of microcarrier types to support cell attachment and growth [41][42][43][44][45][46][47] . Using an alternative design, Papadimitropoulos et al investigated the use of a ceramic scaffold-based perfusion bioreactor for human bone marrow-derived MSC expansion 48 , and Kim and Ma applied a perfusion bioreactor system for the expansion of human MSCs from bone marrow on polyethylene terephthalate (PET) scaffolds 49 .…”
Section: Dynamic Culture Methods Can Enhance Cell Proliferation and Imentioning
confidence: 99%